Cover Feature: Aerobic Conditions Enhance the Photocatalytic Stability of CdS/CdOx Quantum Dots (Chem. Eur. J. 69/2018). Issue 69 (5th November 2018) - Wakerley, David W.; Ly, Khoa H.; Kornienko, Nikolay; Orchard, Katherine L.; Kuehnel, Moritz F.; Reisner, Erwin
Abstract : The H2 evolution activity of CdS/CdO x quantum dots benefits from exposure to air. Photocatalytic H2 production is generally accepted to be strongly inhibited by O2 . CdS/CdO x quantum dots in basic aqueous solution show such rapid H2 evolution that they quickly decompose due to over‐accumulation of electrons. This work shows that aerobic solutions stabilize CdS/CdO x over hours of photocatalysis as O2 can prevent decomposition by removing excess electrons from the quantum dot. This concept can be applied to other photocatalysts, where O2 is considered as a source of inhibition. More information can be found in the Communication by E. Reisner et al. onpage 18385 .